Weaving a magnificent world: 1D fibrous electrodes and devices for stretchable and wearable electronics. Issue 38 (15th September 2022) - Zhang, Wenxiao; Miao, Jinlei; Zuo, Xingwei; Zhang, Xueji; Qu, Lijun
Abstract : One-dimensional fibrous electronics has become one of the most important building blocks for weaving flexible and stretchable electronic devices, which holds great potential in practical wearable applications to weave a magnificent world. Abstract : Emerging soft electronics with excellent mechanical flexibility and conformability can integrate with the human body and clothes seamlessly compared with traditional rigid and bulky electronics. One-dimensional (1D) soft fibrous electronics are highly desirable due to their attractive properties such as lightweight, weaveability, stretchability as well as the ability to adapt frequent mechanical deformations during human activities. Moreover, 1D fibrous electronics have become one of the most important building blocks for weaving flexible and stretchable electronic devices, which holds great potential in practical wearable applications to weave a magnificent world. Here, the state-of-the-art advancement and development in 1D fibrous stretchable and wearable electronics are reviewed, including conductive material systems and structure design strategies, as well as their applications in wearable electronic devices such as conductive fibers, supercapacitors and batteries, and strain sensors. Finally, the critical consideration of the opportunities and challenges of 1D fibrous electrodes and devices for stretchable and wearable electronics are also presented.